Error Analysis in Fraction Arithmetic Operations Among Fourth Grade Students - Nyoto; Mutiara, Annisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study was motivated by the low learning results of mathematics fraction material for grade IV students of SDN-13 Palangka in Palangka Raya city in fraction calculation operations, the problems that arise are what are the types and factors that cause student errors in completing fraction calculation operations. The purpose of this study is to identify the types of errors and factors that cause student errors in solving problems related to fractional calculation operations, The procedure for analyzing student errors used is the Newman procedure. This type of research is a quantitative research with a case study design. Data collection was carried out by test techniques and analysis of student answers on test answer sheets, with 32 research subjects. The data analysis technique uses quantitative descriptive analysis. The questions used for data collection were first tested to determine the distinguishing power and difficulty level of the questions. The results showed that all 32 research subjects made mistakes in each question item with various types of errors, namely concept errors of 45.93%, principles errors of 16.25%, operational errors of 1.87% and errors due to lack of thoroughness of 5%. There are 3 factors that cause students to make mistakes, namely: 1) difficulty understanding concepts; 2) not understanding the principle of fraction operation; 3) and because of forgetting and not being thorough. The factors that cause student errors in solving problems are related to instrumental factors, one of which is the teacher who is incomplete in providing an understanding of mathematical concepts, especially the concept of fractions and their operations.